The Influence of Service Quality towards Revisit Intention to Private Hospitals in Indonesia - Putri J Pratiwi Syam; Hendra Achmadi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The fast-growing number of hospitals in Indonesia resulted in intense competition among hospitals. Hospital must be able to provide a quality health services for patients. Good quality service will establish a harmonious relationship between service providers and patients for the creation of patient satisfaction and profitable patient loyalty. This research was conducted to further examine influence of service quality towards patient’s revisit intention to private hospitals in Indonesia. Quantitative method is used in this study by using 160 subjects gathered as primary data distributed through google forms over the period of January 2022-March 2022. Data collected will then be analyzed using PLS-SEM to evaluate correlation between factors observed. Revisit intention becomes the dependent variable influenced by the independent variable namely reliability, assurance, tangibles, empathy, and responsiveness which are known as service quality. The dependent gave an R square value of 0.676 to the overall rating of the hospital independent variable. Empathy showed to have the strongest influence towards hospital revisit intention with T statistic of 3.665. The service quality of empathy and assurance showed a significant positive effect on revisit intention.